2008
DOI: 10.1167/iovs.08-2134
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Findings in Polypoidal Choroidal Vasculopathy

Abstract: Hyalinization of choroidal vessels, like arteriosclerosis, is characteristic of PCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(170 citation statements)
references
References 39 publications
8
154
0
5
Order By: Relevance
“…Likewise, Kuroiwa et al 23 observed changes mainly in the large choroidal arterioles, showing disruption of inner elastic layer, and deposition of basement membrane-like material and collagen in the vessel wall, suggesting that atherosclerosis of inner choroidal arterioles may be important. Similarly, Nakashizuka et al 24 reported hyalinization of choroidal vasculature, again underpinning the role of atherosclerosis in PCV. In the same study, however, they found no VEGF staining of the vascular endothelium of the polyps, in contrast to previous reports.…”
Section: Pathogenesismentioning
confidence: 84%
“…Likewise, Kuroiwa et al 23 observed changes mainly in the large choroidal arterioles, showing disruption of inner elastic layer, and deposition of basement membrane-like material and collagen in the vessel wall, suggesting that atherosclerosis of inner choroidal arterioles may be important. Similarly, Nakashizuka et al 24 reported hyalinization of choroidal vasculature, again underpinning the role of atherosclerosis in PCV. In the same study, however, they found no VEGF staining of the vascular endothelium of the polyps, in contrast to previous reports.…”
Section: Pathogenesismentioning
confidence: 84%
“…VEGF plays a significant role in the progression of CNV (37), although its role in PCV is controversial (32,33,38,39). We examined the expression of VEGF in the RPE/ choroid of hHTRA1 + mice by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that the abnormal choroidal vessels under Bruch's membrane may permit fluid to leak into the sub-pigment epithelial space with the impairment of the membrane in the early phase. 19,22 However, in majority of the cases, the fine vascular network seemed to be present within or above Bruch's membrane, and may permit fluid leakage into the sub-pigment epithelial space. This would then be compatible with the reported location of the PCV network and polyps.…”
Section: Discussionmentioning
confidence: 98%